The Ability of Students in the Smart Society 5.0 Era in West Sumbawa Regency - Nurdin, Nurdin; khusnarti, khusnarti; Suparman, Suparman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to explore and describe the ability of students in West Sumbawa Regency in facing the era of Smart Society 5.0. Against the backdrop of fundamental changes in the interaction between humans and technology, this research focuses on the educational context in the region. West Sumbawa Regency, which is rich in culture and nature, has also experienced the impact of this change, especially in the context of education. This study used a descriptive qualitative approach involving learners from various levels, teachers, and parents. Data was collected through in-depth interviews, classroom observation, and document analysis. Data analysis is carried out using a content analysis approach to provide an in-depth picture of phenomena that occur in the field. The results showed that most students in West Sumbawa Regency had a fairly good understanding of the concept of Smart Society 5.0. However, there are variations in the depth of understanding, posing challenges and opportunities that need attention. Class observations show that the integration of Information and Communication Technology (ICT) in learning is still in the development stage, with obstacles such as the equitable availability of technology infrastructure needing to be overcome. The discussion of the research results highlighted the importance of students' understanding of Smart Society 5.0 in facing technological changes. Factors such as education level, access to information, and personal experience with technology influence that understanding. ICT integration in learning also needs to be improved by improving teachers' skills and ensuring equitable access to technology across regions. The implications of this research include the development of an educational curriculum that is responsive to the needs of students in the Smart Society 5.0 era and the need for the involvement of related parties, including parents and local communities. In conclusion, a deep understanding and effective integration of technology is the key to improving the ability of students in West Sumbawa Regency to face changing times.